The results of irrigation schemes on input use and yields of sugarbeet in Central Anatolia, Turkey (International Journal of Irrigation and Water Management, 2014)
Today, global climate change and the decrease in ground and surface water sources have increased the importance of the rational and economic use of water as a scarce resource. The selection of irrigation systems in the cultivation of agricultural products is also very important. In this study, sugarbeet which is one of the first established agricultural industries, forms the basis of contract-based production, constitutes a substantial share of farmers income, and requires a great amount of water during its growing stage is examined. The effects of irrigation systems on cost, productivity and level of input use are examined within the scope of Central Anatolia in Turkey where sugarbeet is grown on the largest scale. A comparative calculation is made for irrigation methods widely used in the region, such as sprinkler, furrow and with its increase in recent years, drip irrigation to determine their effect on input use, productivity level and profit in sugarbeet production. It is found that drip irrigation in sugarbeet production allows for saving in input use more than sprinkler and furrow irrigation systems, and that it increases productivity and profit. The spread of especially drip irrigation in sugarbeet production has increased the economic use of water and profitability, through savings in input and reduction of costs.